The Cambridge Intensive Weight Management Programme Appears to Promote Weight Loss and Reduce the Need for Bariatric Surgery in Obese Adults - Golubic, Rajna; Laur, Celia; Kelsey, Megan; Livesy, Alana; Hoensch, Joanna; Park, Adrian; Ray, Sumantra (Frontiers in Nutrition, 2018)
Objectives: To investigate the impact of the Cambridge Intensive Weight Management Programme (IWMP) on weight change, eligibility for bariatric surgery, HbA1c, and blood pressure. Design: Prospective non-randomised intervention Setting: The IWMP is a multi-disciplinary weight loss intervention for severely obese patients to avoid or optimise their physiological state thus enabling bariatric surgery. It uses dietary interventions, pharmacotherapy, and physical activity along with behaviour change counselling. Participants: Severely obese patients (Body Mass Index, BMI≥40kg/m2) Interventions: IWMP is a prospective intervention conducted in a National Health Service Tier 3 obesity service. It includes 3 phases of 8 weeks each: weight loss, weight stabilisation, and weight maintenance. In each phase, patients adhered to a prescribed dietary regime and attended regular clinic visits. Data included in this analysis are from those who enrolled in IWMP between 2009-2013. Primary and secondary measures: The primary outcome was weight change between baseline and completion of the programme. Secondary outcomes included changes in blood pressure, HbA1c and eligibility for bariatric surgery pre-assessment. Changes in outcomes were compared by age, sex, smoking status, and employment. Results: Of n=222 eligible patients, complete data were available for n=141 patients (63.5%). At baseline, the mean(SD) BMI was 49.7 (9.2) kg/m2 for women, and 47.9 (7.2) kg/m2 for men. Mean(SD) weight change for women was -18.64(8.36) kg and -22.46 (10.98) kg for men. N=97 (69%) of patients achieved ≥10% weight loss. Individuals aged ≤50 years lost significantly more weight than those aged >50years (mean(SD) weight loss: 22.18(10.9) kg) vs. 18.32 (7.92) kg, p=0.020). Changes in weight were non-significant by smoking status or employment. Median(IQR) change in systolic and diastolic blood pressure was -6 (-14,6) mmHg and 0 (-8,6) mmHg (non-significant), respectively. There was ~50% reduction in the need for bariatric surgery. Conclusions: For the majority of the patients, IWMP is promoting weight loss and allowing for avoidance of, or optimization before, bariatric surgery.